(untitled) - Kochan, Lionel (London, 1962)
This book begin with the arrival of the Slavs in the 6th century and ends with Gorbachev, the demise of communism and an outline of the Yeltsin years. Greater attention has been paid to developments in Russian provinces and also to the history of arts and cultural life.
Keywords: Soviet union; History